Multi-country analysis of routine data from integrated community case management (iCCM) programs in sub-Saharan Africa - Nicholas P. Oliphant; Maria Muñiz; Tanya Guenther; Theresa Diaz; Yolanda Barberá LaÍnez; Helen Counihan; Abigail Pratt (Edinburgh University Global Health Society, 2014)
To identify better performing iCCM programs in sub-Saharan Africa (SSA) and identify factors associated with better performance using routine data. There is large variation in iCCM program performance in SSA. Four programs appear to be higher performing in terms of treatment rates, treatments per CHW per month, and percent of expected cases treated. Treatment rates for diarrhoea are lower than expected across most programmes. CHWs in many programmes are overtreating pneumonia. Programs targeting larger populations under-five tend to have lower treatment rates. The reasons for lower pneumonia treatment rates where CHWs use RDTs need to be explored. Programs with volunteer CHWs and those with salaried CHWs can achieve similar treatment rates and percent of annual expected cases treated but to do so volunteer programs must manage more CHWs per population and salaried CHWs must provide more treatments per CHW per month.